Food safety, sanitation and hygiene practices among street food vendors in Pokhara, Kaski - Bhandari, Nisha; Bhusal, Babu Ram (Journal of Gandaki Medical College-Nepal, 2021)
Background: Street foods are unique and convenient urban food supply meanwhile it lacks the food hygiene and safety posing major public health risk. Thus, the study aims to identify the food safety, sanitation and hygiene practices of street food vendors.Method: The study is cross sectional including 70 vending units selected conveniently. Structured interview schedule and observation checklist was used as data collection tool.Result: The mean age of the respondent was 38.06 (±10.417) years with >1/2 being females (61.4%). Majority (77.1%) had formal education, 37.1% earns>40,000/month and 86 % had not taken any food hygiene training. Eighty percent of the respondents had fixed stall with about 83% sell freshly cooked food and 75% prepare it in market place. About 84% of the respondent revealed diarrhea as the most prevalent disease caused by poor hygiene. Very less (27%) have their health check-up regularly and about 68.6% prepare food when they are ill. Almost 50% heat food before serving, 58% wash dishes with tap water, 98.6% wash raw food before preparation and all of them wash cooking dishes daily. About half (48.6%) of the respondents re-use oil while cooking. Approximately in 77% refrigeration facility was available. The food vending was found to be good (>50) in 54.3% and sanitation was good (>50%) in 60%.Conclusion: Overall sanitary conditions of the vending sites were good but instead needs improvement in most of the aspect of sanitary condition.